Timing and combinations of cardiovascular diseases in survivors of childhood, adolescent, and young adulthood cancer - Södling, John; Hytting, Jakob; Mallios, Panagiotis; Bollano, Entela; Johansson, Madeleine ; 0000-0001-9057-9148; Rodriguez-Wallberg, Kenny A; Hedayati, Elham; Karlström, Patric; Sundbom, Per; Kiani, Narsis; Keskisärkkä, Robin; Singull, Martin; et al. (Cardio-oncology (London, England), 2025)
BACKGROUND: Children, adolescents, and young adults with cancer (referred to as CAYAs) are at risk of long-term health complications, with cardiovascular disease (CVD) being a major concern. In addition, sociodemographic characteristics and traditional cardiovascular risk factors may also contribute to disparities in outcomes compared with those of the general population. The aim of this study was to investigate the timing, patterns, and combinations of CVDs, as well as associated morbidity, mortality, and sociodemographic factors, in CAYAs with CVD compared with matched controls with CVD. METHODS: A register-based cohort study consisting of all Swedish cancer patients under 25 years old and during a 63-year observation time was used. CAYAs and controls with CVD (n = 58,981) were included and compared in terms of the timing and combinations of CVD, and mortality. RESULTS: The median age at first CVD was 41.8 years in CAYAs and 49.6 years in controls (p < 0.0001), with male CAYAs being the youngest at 25.0 years. During a median follow-up of 34.6 years, most CAYAs (65.2%) developed one CVD, while two or three coexisting CVDs occurred in 20.2% and 8.2%, respectively. Mostly hypertension in combination with cerebrovascular disease, ischemic heart disease and arrhythmias. More than three CVDs were more common in CAYAs than in controls (6.4% vs. 5.9%). A total of 21.8% of the CAYAs died, and the risk of all-cause mortality after the first CVD was 2.43-fold greater (hazard ratio (HR) 95% confidence interval (CI) 2.31-2.54, p < 0.0001), and for cardiovascular mortality, the risk was 2.17-fold greater (HR 95% CI 2.02-2.33, p < 0.0001) than that of the controls. In CAYAs with CVD, older age, male sex, and living in the central part of Sweden were associated with higher mortality, whereas higher education and marriage were protective (p < 0.0001). CONCLUSIONS: Compared with controls CAYAs develop advanced CVD and combinations of multiple CVDs earlier in life, and they have a greater risk of all-cause and cardiovascular mortality. Factors associated with increased mortality risk include male sex and geographic variation, whereas marriage and higher education appear to be protective.
© 2025. The Author(s).